Prevalence and incidence of stroke, white matter hyperintensities, and silent brain infarcts in patients with chronic heart failure: A systematic review, meta-analysis, and meta-regression - Tan, Sean; Ho, Clare Elisabeth Si Min; Teo, Yao Neng; Teo, Yao Hao; Chan, Mark Yan-Yee; Lee, Chi-Hang; Evangelista, Lauren Kay Mance; Lin, Weiqin; Chong, Yao-Feng; Yeo, Tiong-Cheng; Sharma, Vijay Kumar; Wong, Raymond C. C.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Heart failure (HF) is associated with ischemic stroke (IS). However, there are limited studies on the prevalence of IS, white matter hyperintensities (WMHs), and silent brain infarcts (SBIs). Furthermore, interaction with ejection fraction (EF) is unclear. Methods We searched three databases (viz., PubMed, Embase, and Cochrane) for studies reporting the incidence or prevalence of IS, WMHs, and SBIs in HF. A total of two authors independently selected included studies. We used random-effects models, and heterogeneity was evaluated with I2 statistic. Meta-regression was used for subgroup analysis. Results In total, 41 articles involving 870,002 patients were retrieved from 15,267 records. Among patients with HF, the pooled proportion of IS was 4.06% (95% CI: 2.94–5.59), and that of WMHs and SBIs was higher at 15.67% (95% CI: 4.11–44.63) and 23.45% (95% CI: 14.53–35.58), respectively. Subgroup analysis of HFpEF and HFrEF revealed a pooled prevalence of 2.97% (95% CI: 2.01–4.39) and 3.69% (95% CI: 2.34–5.77), respectively. Subgroup analysis of WMH Fazekas scores 1, 2, and 3 revealed a decreasing trend from 60.57 % (95% CI: 35.13–81.33) to 11.57% (95% CI: 10.40–12.85) to 3.07% (95% CI: 0.95–9.47). The relative risk and hazard ratio of patients with HF developing IS were 2.29 (95% CI: 1.43–3.68) and 1.63 (95% CI: 1.22–2.18), respectively. Meta-regression showed IS prevalence was positively correlated with decreasing anticoagulant usage. Conclusion We obtained estimates for the prevalence of IS, WMH, and SBI in HF from systematic review of the literature. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=255126, PROSPERO [CRD42021255126].